Exploring agency problems in the Turkish private pension system :|pension sector employee perspectives - Aslan, Remziye Gül. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
The existing literature on Turkey’s private pension system highlights the limited financial literacy of its participants, which may lead to agency problems. Through a qualitative exploratory study on pension sector employee perspectives, this thesis examines agency problems in the Turkish private pension system in the context of its governance structure. The study relies on semi-structured in-depth interviews with 16 employees from eight pension companies, three portfolio management companies, and one of the regulatory and supervisory organizations. The analysis relies on a thematic content analysis of the interview data. The thesis finds that pension sector employees believe agency problems are prevalent in the private pension system, particularly in the relationship between pension companies and participants. It identifies four major agency problems: the provision of insufficient information to prospective participants, offering pension funds that mismatch participants’ risk preferences, the provision of insufficient information to participants about the performance of their funds, and making investments to their group companies at the expense of participants’ interests. The thesis suggests that these problems may negatively affect the rate of returns for participants and the efficiency of the system. It concludes that the state’s regulatory role of the in the private pension system is more critical in the Turkish case than in countries where secondary pillars are partially monitored through industrial relations in the absence of collective voice mechanism and contract-based governance structure.
Keywords: Pensions -- Turkey.; Pension trusts -- Turkey.